Ludic Application of Augmented Reality (AR) at the National Museum of Natural Sciences in Madrid, Spain - Camps-Ortueta, Irene (2023)
Introduction. The video game Enigma Madrid MNCN, developed by PadaOne Games, is an augmented reality (AR) game designed for the National Natural History Museum (MNCN) in Madrid, Spain. Objective. As a part of the museum experience, it is considered a serious game developed to introduce children to STEM (Science, Technology, Engineering, and Mathematics) subjects. Enigma Madrid MNCN is a new tool that encourages visitors to discover this type of knowledge. Method. This research aims to understand that serious games can increase visitor satisfaction with the museum. To investigate this, 297 children aged between 6 and 13 were invited to play the game for one hour at the museum. Results. The experiment took place at the Museo Nacional de Ciencias Naturales (MNCN) between June 2018 and June 2019. Visitor satisfaction and team play were analyzed in this research. A total of 317 subjects, including 20 adults, participated in the experimental conditions. Half of the sample played alone, and the other half played in pairs. All data were analyzed using SPSS Statistics. Discussion and conclusions. Our findings suggest that visitor satisfaction increases with the video game Enigma MNCN. Additionally, collaboration improves results in the game.